The Mediating Role of Generation Z Customer Satisfaction in the Relationship Between Sharia-Based Customer Service and Customer Loyalty at Bank Syariah Indonesia - Angelika Galis Shaomi Angel Shaomi; Nur Kholidah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In Islamic banking, sharia-based customer service has an important role in encouraging sustainable relationships with Generation Z customers, who tend to assess service quality critically and have high expectations toward service performance. The research addresses whether value-based customer service directly translates into brand loyalty or if it requires an intermediate emotional response. Consequently, the primary objective is to evaluate how Sharia-based service quality contributes to loyalty formation among Generation Z customers in Bank Syariah Indonesia through the presence of customer satisfaction as an intermediate mechanism. The study adopted a quantitative design and employed the Structural Equation Modeling technique to process primary data gathered from 94 eligible respondents. The analytical model focused on both technical service dimensions and Islamic ethical values, such as integrity and empathy. The findings reveal that while Sharia-inspired customer service significantly boosts satisfaction, it fails to produce a direct measurable effect on customer loyalty. Instead, the results demonstrate a "full mediation" effect; satisfaction acts as the essential bridge, where high-quality service leads to contentment, which subsequently drives loyal behavior. This suggests that for the younger generation, loyalty is not an immediate reaction to service encounters but a gradual outcome of meeting their specific expectations for ethical and professional excellence.